2018
DOI: 10.1016/j.apnu.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Resilience from the Perspectives of Caregivers of Persons with Dementia

Abstract: This paper is NOT THE PUBLISHED VERSION; but the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in the citation below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…Most caregivers were women (wives or mothers), with a mean age of 68 years. In the 3 qualitative studies, 27,38,41 the samples included mostly caregivers of patients with a chronic disease, patients in a vegetative state, 30 and patients with Alzheimer disease. 41…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most caregivers were women (wives or mothers), with a mean age of 68 years. In the 3 qualitative studies, 27,38,41 the samples included mostly caregivers of patients with a chronic disease, patients in a vegetative state, 30 and patients with Alzheimer disease. 41…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that resilience can reduce anxiety, depression, perception of pain, and emotional distress as well as it enables adaptation promoting effective coping strategies and positive affect in the context of oncological illness. 5,31,33,40,41,43 -49…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, caregivers describe feelings of confusion, uncertainty, sense of isolation, and disbelief [6][7][8]. Sense of loss, fear, and anger have also been reported by caregivers [6,9]. In addition, previous research has shown that almost half of dementia caregivers meet the diagnostic criteria for clinical depression and the spouses of persons with dementia are four time more liable to develop depression as compared to spouses of persons without dementia [2,10,11].…”
mentioning
confidence: 99%